KONSEP SABAR DALAM AL-QUR’AN: STUDI TAFSIR TEMATIK TERHADAP AYAT-AYAT SABAR - Attoriq Islami Pasha; Muhammad Fahrul Ihsan; Hikmatul Luthfi (Adisam Publisher, 2026)
This study aims to examine the concept of sabr patience in the Qur’an through a thematic exegesis approach by analyzing verses related to patience. In modern psychological studies, the concept of patience is often associated with resilience, emotional regulation, and self-control, but it tends to focus primarily on psychological aspects. Meanwhile, the Qur’an views sabr as a broader concept because it integratively encompasses spiritual, emotional, and social dimensions. Therefore, this study is conducted to construct a conceptual understanding of sabr from a Qur’anic perspective. This study employs a qualitative approach using the thematic exegesis method (tafsir maudhu‘i). The research data consist of Qur’anic verses related to the concept of sabr, which are analyzed through a process of thematic categorization based on semantic relevance. To strengthen the interpretation, this study refers to classical and contemporary exegetical works, such as Tafsir Ibn Kathir, Tafsir Al-Qurtubi, and Tafsir Al-Misbah. The findings show that the concept of sabr in the Qur’an is divided into three main themes: (1) sabr as a spiritual strength, related to steadfastness of faith and belief in Allah’s help; (2) sabr as emotional regulation and self-control, functioning as a religious coping mechanism in facing life’s pressures; and (3) sabr as social relations and solidarity, emphasizing the importance of empathy, tolerance, and mutual advice in social life. These findings indicate that sabr from a Qur’anic perspective is not only understood as the ability to endure trials, but also as a process of self-transformation that comprehensively integrates spiritual, emotional, and social dimensions.